A Internet como Suporte da Leitura Literária: A Leitura da Poesia no Blog - Ribeiro, Gilsa Elaine de Lima (2011)
On the global relations between literature and media, the Internet emerges as a medium for the dissemination and reading of literary work. This method of disclosure ultimately demonstrates the subject´s need to share his thoughts on politics, philosophy, art, and express his literary tastes through writing. Regarding the latter, Web surfers use blogs, our object of study, to disseminate both poems by renowned authors of the literary canon as well as their own poems. Thus, in an analytical perspective about the way the reading of poetry in that medium happens, theoretical notions of the reader were taken in consideration, support, reading, blog and cyberspace, through recent studies on the relationship between the reader and the medium used to read considering that when the support changes, the reading forms change, besides the theoretical regarding cyberculture. This dissertation aims to understand how poetry reading occurs in the blogs, reflecting the way they circulate, as they are read and approved in cyberspace, on the view that poetry is gaining readers and being a motivational tool for its reading. For this purpose, we created a blog to supporte our analysis. Considering the popularity of blogs and resources, we bring this support as an additional tool for the poetry reading in schools, creating theoretical and methodological alternatives to help teaching process and reading of poetry on this medium, using as a strategy the construction of other blogs by high school students, which are coordinated during a certain period, through a research, at times, based on ethnographic research.